DNA extraction bias influences resistome profiles in seahorse skin microbiomes - ROSE CHINLY MAE ORTEGA-KINDICA; JOSE LUIS BALCAZAR; SHARON ROSE M. TABUGO (Society for Indonesian Biodiversity, 2025)
Abstract. Ortega-Kindica RCMH, Balcazar JL, Tabugo SRM. 2025. DNA extraction bias shapes resistome profiles in seahorse skin microbiomes. Biodiversitas 26: 5049-5056. Antimicrobial Resistance Genes (ARGs) are emerging environmental risks, particularly in coastal environments impacted by anthropogenic activities. Seahorses (Hippocampus spp.), as benthic and ecologically sensitive species, are in constant contact with biofilm-enriched sediments and can act as bioindicators of environmental ARGs. Their unique ecological niche and sensitivity to environmental changes make them ideal candidates for monitoring ARGs in marine ecosystems. In this study, the skin microbiome of Hippocampus barbouri was analyzed using shotgun metagenomics to assess the impact of two commercial DNA extraction kits, the HiMedia Water DNA Purification Kit (HMS) and the Qiagen DNeasy PowerSoil Pro Kit (QKS), on the detection of ARGs. DNA was extracted from the skin microbiome of 30 adult H. barbouri (Barbour's seahorse) collected from Cantiasay Island, Surigao del Norte, Philippines, and subsequently subjected to shotgun metagenomic sequencing. Across the samples, 17 ARG families were found with recovery varying between the extraction kits. The QKS kit yielded higher DNA concentrations and revealed a broader range of ARGs, including multidrug, macrolide, and ?-lactam. In contrast, the HMS kit recovered fewer ARG categories, possibly due to reduced cell lysis efficiency or the presence of inhibitors. Statistical analyses (p<0.05) confirmed significant kit-dependent differences in resistome profiles. These findings highlight that DNA extraction protocols can influence ARG detection and emphasize the need for rigorous methodological standardization in metagenomic studies. Furthermore, the detection of diverse ARGs in the skin microbiota of H. barbouri supports its potential as a sentinel species for environmental resistome monitoring in marine ecosystems.